2019
DOI: 10.1111/exd.13956
|View full text |Cite
|
Sign up to set email alerts
|

The mechanism for differential effect of nelfinavir and indinavir on collagen metabolism in human skin fibroblasts

Abstract: The mechanism for differential effects of human immune deficiency virus protease inhibitors (HIVPIs), nelfinavir (NEL) and indinavir (IND) on collagen metabolism disturbances was studied in human skin fibroblasts. It has been considered that HIVPIs‐dependent deregulation of collagen biosynthesis involves prolidase (an enzyme providing proline for collagen biosynthesis), glutamine (Gln) (a substrate for proline biosynthesis), nuclear factor‐κB (NF‐κB) (a transcription factor that inhibit expression of type I co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…It suggests that exogenous Pro has lower than Gln influence on collagen biosynthesis. Recently we found that Pro deficiency resulting from a lack of Gln may be partly supplemented by recovery of Pro from imidodipeptides, intermediate products of protein degradation [54]. Thus, it can be concluded that fibroblasts prefer exogenous Gln, as an intermediate of proline for effective collagen biosynthesis.…”
Section: Role Of Proline and Glutamine In Regulation Of Collagen Biosmentioning
confidence: 99%
“…It suggests that exogenous Pro has lower than Gln influence on collagen biosynthesis. Recently we found that Pro deficiency resulting from a lack of Gln may be partly supplemented by recovery of Pro from imidodipeptides, intermediate products of protein degradation [54]. Thus, it can be concluded that fibroblasts prefer exogenous Gln, as an intermediate of proline for effective collagen biosynthesis.…”
Section: Role Of Proline and Glutamine In Regulation Of Collagen Biosmentioning
confidence: 99%
“…The important role of proline recycled by prolidase has been shown in both normal and cancer cells. In dermal fibroblasts, cells addicted to proline due to extensive biosynthesis of extracellular matrix components, induction of prolidase stimulated TGFβ signalling ( Surazynski et al, 2010 ), and collagen biosynthesis ( Shim et al, 2012 ; Szoka et al, 2019 ). In breast cancer, proline released by prolidase was found to regulate HIF-1α expression ( Surazynski et al, 2013 ) and stimulate autophagy ( Zareba et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Hydrolysis of this bond in dipeptides released from proteins, and thus the final stage of protein degradation, is catalysed by cytoplasmic prolidase ( Wilk et al, 2017 ). The importance of prolidase for supplementing proline during its shortage has been demonstrated on the example of biosynthesis of collagen, a protein containing high proline residue content ( Shim et al, 2012 ; Szoka et al, 2015 ; Szoka et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, it's potentially life‐threatening and multiple organ sites‐affecting variant, systemic sclerosis (SSc), has long been in the spotlight of skin research. A number of novel pathways regulating fibroblast activation and tissue fibrosis beyond the profibrotic ‘master’ regulator transforming growth factor‐β 1 (TGF‐β 1 ) have been identified 71‐81 . For example, the expression of Dickkopf‐1, a natural Wnt antagonist, was shown to be altered in skin of patients with SSc 72 .…”
mentioning
confidence: 99%